L’efficacité du droit OHADA dans un contexte de convergence, concurrence et harmonisation des systèmes juridiques - Sangare, Salif (Université de Montréal, 2026)
Cette étude entend contribuer au développement économique des États d’Afrique subsaharienne francophone, notamment ceux membres de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA). En effet, les États qui constituent l’espace communautaire avaient déjà chacun dans leur sein des dispositions chargées de régir les activités économiques. Cependant, avec le temps, la disparité des normes régissant ces activités est apparue comme un frein à l’émergence économique de ces États. C’est dans ce cadre qu’ils ont décidé, lors de la signature du 17 octobre 1993 instituant l’OHADA, de mettre en place un droit commun des affaires en mesure de faciliter leur intégration juridique en promouvant le développement économique. Ce droit se veut « harmonisé, moderne et simple ». Si l’organisation a, à ce jour, adopté onze Actes uniformes couvrant plusieurs pans du droit des affaires en vue de réaliser la croissance économique prévue dans le Traité, il est important de souligner que le droit issu de l’OHADA souffre d’une certaine lourdeur liée à son enracinement non africain. Aussi, l’harmonisation du départ considérée comme le fer de lance de l’Organisation s’est matérialisée sur le terrain par une uniformisation du droit des États membres dans une société traversée par le multiculturalisme. Cette situation peut être de nature à contraindre les mœurs par le droit. On peut également ajouter à cela, le fait que le droit issu de l’OHADA est marqué par le sceau du mimétisme juridique en ce qu’il ne prenne pas en compte le secteur informel qui occupe une place très importante dans les relations d’affaires. Enfin, puisque l’enchâssement de la loi dans l’identité culturelle est l’une des conditions déterminantes de son efficacité, les précurseurs du droit OHADA auraient tout à gagner en faisant ressortir le droit OHADA des valeurs des sociétés africaines, sinon, le développement économique tant recherché de l’Afrique n’aura pas lieu. This study aims to contribute to the economic development of French-speaking sub-Saharan African countries, particularly those that are members of the Organization for the Harmonization of Business Law in Africa (OHADA). Indeed, the states that make up the community already had provisions in place to govern economic activities. However, over time, the disparity in the standards governing these activities has emerged as an obstacle to the economic emergence of these states. It was in this context that, when signing the agreement establishing OHADA on October 17, 1993, they decided to put in place a common business law capable of facilitating their legal integration by promoting economic development. This law aims to be “harmonized, modern, and simple.” While the organization has, to date, adopted eleven Uniform Acts covering several areas of business law with a view to achieving the economic growth envisaged in the Treaty, it is important to note that OHADA law suffers from a certain cumbersomeness due to its non- African roots. Thus, the harmonization that was initially considered to be the Organization's spearhead has materialized in practice as a standardization of the laws of member states in a society marked by multiculturalism. This situation may be such as to constrain customs through the law. To this can be added the fact that OHADA law is marked by legal mimicry in that it does not take into account the informal sector, which plays a very important role in business relations. Finally, since the embedding of law in cultural identity is one of the determining conditions for its effectiveness, the precursors of OHADA law would have everything to gain by highlighting the values of African societies in OHADA law; otherwise, the much sought-after economic development of Africa will not take place.
Keywords: Acte uniforme; African societies; Cultural diversity; Diversité culturelle; Droit OHADA; Développement économique; Economic development; Efficacité; Efficiency; Harmonisation; Harmonization; Intégration juridique; Legal integration; OHADA law; Sociétés africaines; Standardization; Uniform Act; Uniformisation

The role of the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in facilitating continental integration - Luthuli, Isaac (University of KwaZulu-Natal, 2020)
The dissertation examines the role the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) can play in facilitating the political and economic convergence of the African Union (AU) member states. The developmental challenges facing Africa in spite of its wealth of human and natural resources is poignant. The genesis of this problem can be traced to the history of colonialism and the wave of independence in the continent in the late 1950s. Arguments have been put forward to suggest that one of the most viable ways of promoting Africa’s development is by developing and promoting intra-continental trade which can be possible through continental integration. The specific areas reviewed are regional stability and how intra-regional trade and investment is used to promote economic convergence. Africa's need for political and economic integration at a continental level is further sustained by the assumption that neocolonialism can be blamed for the weakness of structures in African states. Some scholars agree on the idea that regionalisation is often seen to offer a possibility to respond to the challenges of globalization. This impact nevertheless is dependent on the relation between globalisation and regional sentiment. Regional integration implies a form of interdependence among nation-states. Such interdependence leads to an establishment of regional integration arrangements between sovereign states within a geographical space. These agreements are shaped formally and there is a commitment to work together in order to realise political and socio-economic benefits. This study maintains that in order to achieve effective integration of the continent, Nigeria and South Africa as case studies, as continental giants have a key role to play to this end and as members of ECOWAS and SADC respectively. It is argued here that both the SADC and ECOWAS as sub-continental blocks have made some notable and commendable progress in developing policies for trade liberalization and economic integration, this, however, is not enough as such policies are also pertinent at a continental level. The study found that SADC and ECOWAS as regional blocks can play a role in aiding the continent to achieve a trade liberalization to achieve continental economic development.
Keywords: African integration; ECOWAS; Economic Development; Economic convergence; Integration; Intra-continental trade; SADC